Nilai Moral dalam Novel Dia Suamiku Karya Reni Juniarti - Fitri Yanti; Delia Putri; Rita Arianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the moral values ​​contained in the novel Dia Suamiku by Reni Juniarti. This research method is a descriptive method with a qualitative research type. The results of this study were found 38 data on moral values ​​in the novel Dia Suamiku by Reni Juniarti, of the 38 data grouped into 3 types of moral values, namely, 1) the relationship between humans and their gods as many as 10 data, which were classified into 3 types, namely belief values, 7 data. , the value of gratitude 0 data and prayer 3 data ; 2) human relationship with oneself as many as 11 data which are classified into 3 types, namely firm stance with 2 data, optimistic with 3 data, regret 6 data; 3) human relations with other humans in the social sphere as many as 17 data are classified into 3 types, namely the value of caring for 12 data, grateful for 1 data and appreciating as much as 4 data. The most dominant moral values ​​found are the moral values ​​of human relations with other humans in the social sphere, especially the value of caring, which is 12 data. In conclusion, in this novel the value of caring is very dominant because the kinship and togetherness between the characters are well established, they love and care for each other so that their concern is very strong for others. Keywords: Dia Suamiku, Morals, Values, Novel